Quality Improvement Analysis of Timing Chain Cover Components Using Six Sigma DMAIC in an Automotive Component Assembly Line - Rizky Fari Riandy; Agus Suwarno; Annisa Syahliantina (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
Product quality is a critical factor in maintaining process stability and competitiveness in the automotive component manufacturing industry. An automotive component manufacturing company in Karawang, Indonesia, experienced quality problems in the Timing Chain Cover assembly process, particularly porosity and dantsuki defects. This study aims to analyze the defect rate, identify dominant critical-to-quality (CTQ) defects, evaluate process capability, determine potential defect causes, and propose improvement and control actions using the Six Sigma DMAIC approach. The research used production and quality inspection data from January to June 2025. The analysis was conducted through the Define, Measure, Analyze, Improve, and Control stages using defect rate, Defect Per Unit, Defects Per Million Opportunities, sigma level, p-chart, Pareto analysis, fishbone diagram, and 5W+1H improvement planning. The results showed that 1,142 CTQ defects were found from 64,130 units produced, consisting of 611 porosity defects and 531 dantsuki defects. The average defect rate was 1.78%, exceeding the company’s internal target of less than 1.5%. The average DPMO value was 8,899, with a process capability level of 3.87 sigma. The p-chart result indicated that the process was statistically stable, but stable at a defect level that remained above the company target. The potential causes of defects were related to machine parameter stability, mould condition, SOP compliance, inspection discipline, material handling, measurement control, and workplace conditions. This study proposes prioritized improvement actions and a measurable control plan as recommendations for future implementation. The findings provide a practical DMAIC-based framework for identifying dominant defects, evaluating process capability, and developing structured quality improvement strategies in automotive component assembly processes.